The Impact of COVID-19 Pandemic on ESBL-Producing Enterobacterales Infections: A Scoping Review - Ha Thi Thao Mai; J. Luis Espinoza (MDPI AG, 2023)
Several studies have reported an increased frequency of colonization and/or infection with antibiotic-resistant bacteria (ARB) during the COVID-19 pandemic. Extended-spectrum beta-lactamase-producing Enterobacterales (ESBL-PE) are a group of bacteria with intrinsic resistance to multiple antibiotics, including penicillins, cephalosporins, and monobactams. These pathogens are easy to spread and can cause difficult-to-treat infections. Here, we summarize the available evidence on the impact of the COVID-19 pandemic on infections caused by ESBL-PE. Using specific criteria and keywords, we searched PubMed, MEDLINE, and EMBASE for articles published up to 30 March 2023 on potential changes in the epidemiology of ESBL-E since the beginning of the COVID-19 pandemic. We identified eight studies that documented the impact of COVID-19 on ESBL-E. Five studies were focused on assessing the frequency of ESBL-PE in patient-derived specimens, and three studies investigated the epidemiological aspects of ESBL-PE infections in the context of the COVID-19 pandemic. Some of the studies that were focused on patient specimens reported a decrease in ESBL-PE positivity during the pandemic, whereas the three studies that involved patient data (1829 patients in total) reported a higher incidence of ESBL-PE infections in patients hospitalized for COVID-19 compared with those with other conditions. There are limited data on the real impact of the COVID-19 pandemic on the epidemiology of ESBL-PE infections; however, patient-derived data suggest that the pandemic has exacerbated the spread of these pathogens.